Culture conversion and six months interim outcomes in retreatment cases of pulmonary MDRTB- a six month interim analysis - Batool, Rabab; Khan, Sher Wali; Mohammad Imran; Barry, Zainab; Sheikh Zafar Ali (Journal of the Pakistan Medical Association, 2021)
Background: Multi-Drug Resistant Tuberculosis (MDRTB) is difficult to treat form of TB, retreatment of MDRTB patients is a more difficult area as patients have modified drug resistant patterns, more number of least effective drugs on the regimen and the cure rates are low. Objectives: The Objectives of this study were to estimate the time to culture conversion and factors associated with failure to culture conversion, six months interim outcomes and associated risk factors with poor interim outcomes in MDRTB patients who had been previously treated with second line drugs. Methods: The study was Prospective clinical case series study. All bacteriologically confirmed MDRTB retreatment patients enrolled between March-2016 to January-2017 at TB Clinic: The Indus Hospital and seven other Programmatic Management of Drug Resistant Tuberculosis (PMDT) sites (n=266) running under the umbrella of TB Clinic-The Indus Hospital were enrolled into the study. Results: Overall, 40.1% of MDR retreatment patients experienced poor interim outcome. Poor interim outcomes were significantly associated with higher number of drugs on the regimen, (OR= 1.27, 95% CI: 1.03-1.58) and high sputum smear grading (OR=4.56, 95% CI: 3.30-18.71). Almost 70.3% patients experienced culture conversion within initial six months of treatment. Conclusion: The success rate of retreatment of MDRTB with conventional regimen is unacceptably low. Key words: Multi-drug Resistant Tuberculosis, Second Line Drugs, Culture Conversion, Interim Outcomes, Sputum Smear Microscopy